Ergonómiamérések a fluidumáramban = Ergonomic measuring in fluidum flows - Sándor Ágnes (Taylor : gazdálkodás- és szervezéstudományi folyóirat, 2016)
The topic of rethinking, reorganizing or reengineering dysfunctional business processes has been approached from many aspects. However, methods and techniques are greatly diverse. Service processes do not get as much attention as their importance would deserve. One reason is the usage of production-oriented methods for service processes. The other reason is the complexity of stochastic service processes. In these processes, it is usually hard to give strict and consistent parameters, indicators and even object functions. It is also a common problem with dysfunctional processes, when due to legislation issues the structure of the process cannot be changed. In these cases a solution could be the swapping rotation of users on process nodes. To illuminate this problem, and to find an effective swapping methodology of rotation we are performing a simulation model. In this paper the system approach of this model is presented.